2014
DOI: 10.1186/preaccept-1041462276129106
|View full text |Cite
|
Sign up to set email alerts
|

Immunological markers of Plasmodium vivax exposure and immunity: a systematic review and meta-analysis

Abstract: Background: Identifying Plasmodium vivax antigen-specific antibodies associated with P. vivax infection and protective immunity is key to the development of serosurveillance tools and vaccines for malaria. Antibody targets of P. vivax can be identified by seroepidemiological studies of individuals living in P. vivax-endemic areas, and is an important strategy given the limited ability to culture P. vivax in vitro. There have been numerous studies investigating the association between P. vivax antibody response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 60 publications
3
43
1
Order By: Relevance
“…The response to the highly conserved phosphoriboprotein peptide P2 was similar to that observed for MSP‐1 and better than that of AMA‐1, suggesting P2's potential as a diagnostic candidate. Both anti‐MSP‐1 and anti‐AMA‐1 responses are generally found to correlate well with vivax infection . We found a 50% positivity rate for these antigens in our cohort.…”
Section: Discussionsupporting
confidence: 54%
“…The response to the highly conserved phosphoriboprotein peptide P2 was similar to that observed for MSP‐1 and better than that of AMA‐1, suggesting P2's potential as a diagnostic candidate. Both anti‐MSP‐1 and anti‐AMA‐1 responses are generally found to correlate well with vivax infection . We found a 50% positivity rate for these antigens in our cohort.…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, a meta-analysis study discuss that despite a great heterogeneity of humoral response observed where P . vivax infection is endemic, IgG response to a number of antigens is associated with increase antibody levels [46]. The same is observed when the dynamics of the antibody response is assessed during P .…”
Section: Discussionmentioning
confidence: 93%
“…Antibodies are important biomarkers in a broad range of diseases, and especially important for the diagnosis and surveillance of infectious diseases, autoimmune diseases and allergies. [1][2][3][4] In addition, antibody-based drug therapies constitute an important part of newly introduced drugs, in particular in the field of oncology and inflammatory diseases. 5,6 While a wide variety of sensitive antibody detection strategies have been developed, many of them come with intrinsic limitations such as the requirement for multiple time-consuming incubation steps (ELISA), multiple reagents or sophisticated equipment (Luminex, SPR).…”
mentioning
confidence: 99%